Władza państwowa a społeczeństwo polskie i przemiany polityczne w XIX–XXI stuleciu - Wapiński, Roman (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
Contemporarily, in the twenty-first century, many scholars of Polish history not only those researching modernity and the most recent times follow – sometimes blindly – in the footsteps of their predecessors who examined it in the post-partitions era, in the political climate which favored the idealization of the Commonwealth of Two Nations and its identifi cation with Poland. In those times such an attitude might have been at least partly justifi ed and excused because it made defining and spreading of Polish national traditions a lot easier and therefore helped shape Polish national community. However, even then this attitude made it difficult for Polish political thinkers and activists to recognize many complex consequences of the long existence of multiethnic and multicultural Commonwealth and of living on the Polish-Ruthenian-Lithuanian border. This form of statehood can only partly be legitimately treated as a form of Polish statehood. It is so not only because of the fact that the proportion of Ruthenian lands in the Commonwealth had been gradually increasing since the fourteenth century, but also, among other things, because since that time we can observe a steady advance of the processes leading to the increase in freedom and rights of only one social state, i.e. nobility, and to the corresponding weakening of the role played by federal government, especially by its executive branch. The infl uence which was exerted by the living conditions of Polish community under partitions on the relations between state and society in reborn Poland 1918–1939 is quite well recognized. It is useful to remember that at the beginning of the most recent history of Poland, which for obvious reasons was up to 1918–1920 conceptualized as the history of national community, these relations were in far less beneficial shape than in the most Western European countries. In the Russian Empire Polish people, similarly to other inhabitants, were treated as subjects moreover, a second category subjects. In two remaining states, which participated in partitions, Polish people benefited from their progressive democratization since the turn of the nineteenth century, but the significant diminishing of the distance between authorities and Polish population happened only on the territory subject to Austrian rule because it was granted national autonomy. However, the causes of the gulf between state and society in Poland cannot be sought out exclusively in the post-partition era. The majority of the population of the Commonwealth of Two Nations particularly peasants who were as much members of the imagined Polish community as of Lithuanian or Ruthenian, i.e. Ukrainian or Belarusian one practically did not come into any significant contact with state authorities, at least on a day-to-day basis.
Keywords: władza państwowa; społeczeństwo polskie; XIX-XXI wiek; Polska